PERBAIKAN TANAH PROBLEMATIK LEMPUNG LUNAK DENGAN METODE STABILISASI KIMIAWI DITINJAU DARI NILAI KADAR AIR DAN INDEKS PLASTISITAS - S Syahril; Agus Suyono; Muchtar Muchtar; Hendry Hendry; Rio Prajudi; Raihan Riandi (Politeknik Negeri Semarang, 2022)
Soft clay soils generally have unfavorable characteristics or properties, when used as a basis for a construction. The characteristics of soft clay soil are having high soil compressibility, low carrying capacity, low permeability value, being cohesive and having a high level of soil activity. One form of effort to improve the characteristics of the soil's bad properties is to carry out stabilization. Stabilization is an activity of mixing soil with certain materials, and is expected to react with the soil, so that the soil characteristics become better. The methodology applied in this study is chemical stabilization, with mineral materials in the form of marble ash waste with 4 different types of variants. Based on the test results, there was a decrease in the value of the water content and soil plasticity index (PI) of 44.94% in variant 3 (20% marble ash waste) compared to the original soil. It is estimated that there is a reaction from the marble ash on soft clay soil, namely in the form of absorption of excess water contained in the soil and voids contained in the soil filled with marble waste, so that the adhesion between particles becomes better.